Communication Strategy for Children with Speech Delay - EDHY RUSTAN (Ta'dib: Jurnal Pendidikan Islam, 2019)
Delay in talking to children certainly has an impact on the stages of its development so that it requires a communication strategy from both parents and teachers to stimulate the child's speaking ability. This study aimed to describe the application of communication strategies and the effect of their application on children's communication skills. This research is qualitative research using a case study method involving students, parents and kindergarten teachers in Jumni City, Palopo. The results of observations and interviews were then analyzed using thematic content analysis techniques. Based on observations and interviews conducted, it was found that parents implemented various strategies, such as speaking slowly and clearly, routinely inviting talking and using hand movements. While, the teacher implements strategies to correct word pronunciation errors, invites storytelling and uses body movements. Through the application of this strategy, the child's ability to speak is getting better and the principle of two-way communication can occur where students are able to channel their desires, imagination, and emotions. Thus, it is hoped that communication strategies can be developed and implemented by parents and teachers to the fullest.